N-TiO2-x Nanocatalysts: PLAL Synthesis and Photocatalytic Activity. (11th June 2020) - Fazio, Enza; Mezzasalma, Angela Maria; D'Urso, Luisa; Spadaro, Salvatore; Barreca, Francesco; Gallo, Giovanni; Neri, Fortunato; Compagnini, Giuseppe
Abstract : N-TiO2- x nanocatalysts are developed by the pulsed laser ablation in liquid (PLAL) technique, a simple and surfactant-free preparation method. The PLAL approach allows synthesizing chemical-morphological fine-tuning water TiO2 -based nanomaterials, starting from targets of different nature (powders and commercial high purity targets). The catalytic activity was investigated using methylene blue (cationic dye) and methyl orange (azo dye). A different photocatalytic response was found for the various kinds of N-TiO2- x . In the first 20 min, under UV and visible light, about 50% and 10% of the methyl orange were removed using the N-TiO2- x and TiO2 colloids, respectively. In addition, we observe that the response towards the methylene blue is comparable in all the synthesized samples under UV irradiation while differing by about 30% under a visible lamp. The enhanced photocatalytic response of the N-TiO2- x nanocatalysts with respect to the TiO2 one is dependent on the content of the nitrogen dopant, surface area, and nitrogen-oxygen bonding configurations.